The Equivalence and Translation Strategies of English-Indonesian Circumstances in a Novel The Kite Runner - Gina Fitri Shabrina; Ni Luh Putu Setiarini (International Journal of English and Applied Linguistics (IJEAL), 2023)
In the clause structure, circumstantial constituents are an important part because their role is to provide an explanation of the environment or circumstances that accompany a process in the clause. To translate this, it is required to determine the appropriate translation strategies. This research analysed translation strategies that are used to translate English circumstances in The Kite Runner novel. The aims of this research is to clarify, define the translation strategies made used for the circumstances that are shown in the target text in conjunction with the source text, and to serve as answers to the questions regarding the types of translation strategies the translator employs and why they are used in the target text by using qualitative research by making use of Halliday and Matthiessen’s (2013) Systemic Functional Linguistics circumstance classifications and Chesterman’s (2016) translation strategies. The data for this research was taken from the circumstances found in the English version of The Kite Runner novel, which serve as the source language and the Indonesian version as the target language that shows the translated circumstances as the primary data. The findings of this research showed that there are eight types of circumstances in The Kite Runner novel and nine translation strategies that the translator of the novel used to translate the circumstances found in the Indonesian version of this novel. The results also showed that the most prevalent translation strategy for translating the circumstances in The Kite Runner novel is literal translation by translating them completely and accurately.